2007
DOI: 10.21608/jpp.2007.221155
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Some Rootstocks on Performance of Superior Grape Cultivar

Abstract: The present investigation was conducted during the period from 2001 to 2006, to study the influence of some grape rootstocks on Superior cultivar. Two stages were involved in this study; the first included bench grafting of Superior cultivar on Dogridge, Salt creek, Freedom, Harmony, SO4, Teleki 5C, Paulsen 1103 rootstocks. The following determinations were carried out: percentage of grafting success, vegetative growth of shoots and roots, fresh and dry weight, relative water content, chlorophyll and cation ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…In addition, the author found that chemical characteristics of berries (soluble solids content, titratable acidity, and SSC/acid ratio) were significantly affected by the used rootstock type compared to ownrooted vines. Our results are in the same line with those of Bica et al (2000), Nikolaou et al (2000), Keller et al (2001), Bavaresco et al (2003), Fisarakis et al (2004), El-Morsi et al, (2006, Somkuwar et al (2006), Gaser (2007), El-Banna, et al (2009), Satisha et al (2010), Rizk-Alla et al (2011), Desouky et al (2015), Hifny et al, (2016), Kamila and Ochmian (2018), Mervat et al (2019), Ghule et al (2021, Mohsen (2021 and Graff et al (2022).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the author found that chemical characteristics of berries (soluble solids content, titratable acidity, and SSC/acid ratio) were significantly affected by the used rootstock type compared to ownrooted vines. Our results are in the same line with those of Bica et al (2000), Nikolaou et al (2000), Keller et al (2001), Bavaresco et al (2003), Fisarakis et al (2004), El-Morsi et al, (2006, Somkuwar et al (2006), Gaser (2007), El-Banna, et al (2009), Satisha et al (2010), Rizk-Alla et al (2011), Desouky et al (2015), Hifny et al, (2016), Kamila and Ochmian (2018), Mervat et al (2019), Ghule et al (2021, Mohsen (2021 and Graff et al (2022).…”
Section: Discussionsupporting
confidence: 91%